An Analysis of Sue Ann™s Personality Development in Ma 2019 - Lubis, Widya Febriani; Murni, Sri Minda (TRANSFORM: Journal of English Language Teaching and Learning, 2022)
This study deals with the characterization of Sue Ann as the main character in Ma film and it was aimed to knowing the characteristics of personality development of Sue Ann.  It was conducted by applying descriptive qualitative method. The source of the data was taken from the dialogues and pictures of characterization of main character found in Ma film. The data were collected by using documentation technic. The data were analyzed by using descriptive qualitative analysis. The findings of this study showed that the characteristics of Sue Ann™s before she met Ben Hawkins and after she met him. There were factors that influence the changes of personality development by Hurlock (1976) included those condition are physical changes, environment, significant people, and social pressure. The factors affecting the change of Sue Ann™s personality, Sue Ann become Neuroticism/Negatively person, her behaviors and actions were changed such as depression and take revenge person.